Azure DevOps Server 2019 Cookbook : Proven recipes to accelerate your DevOps journey with Azure DevOps Server 2019 (formerly TFS), 2nd Edition /: Proven recipes to accelerate your DevOps journey with Azure DevOps Server 2019 (formerly TFS), 2nd Edition. (2019) - Arora, Tarun; Shigihalli, Utkarsh
No abstract available